2019
DOI: 10.1513/annalsats.201807-441oc
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Tolerability of Comprehensive Research Bronchoscopy in Chronic Obstructive Pulmonary Disease. Results from the SPIROMICS Bronchoscopy Substudy

Abstract: Rationale: There is an unmet need to investigate the lower airways in chronic obstructive pulmonary disease (COPD) to define pathogenesis and to identify potential markers to accelerate therapeutic development. Although bronchoscopy is well established to sample airways in various conditions, a comprehensive COPD research protocol has yet to be published.Objectives: To evaluate the safety and tolerability of a comprehensive research bronchoscopy procedure suitable for multicenter trials and to identify factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 41 publications
(50 reference statements)
0
26
0
Order By: Relevance
“…Nevertheless, we acknowledge that the occurrence of COPD exacerbations may in part have been influenced by the bronchoscopic interventions, which included multiple cryobiopsies. To put this rate into context, an analysis of the SPIROMICS (Subpopulations and Intermediate Outcome Measures in COPD Study) trial demonstrated a 27% rate of respiratory complications after research bronchoscopy performed in patients with COPD ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, we acknowledge that the occurrence of COPD exacerbations may in part have been influenced by the bronchoscopic interventions, which included multiple cryobiopsies. To put this rate into context, an analysis of the SPIROMICS (Subpopulations and Intermediate Outcome Measures in COPD Study) trial demonstrated a 27% rate of respiratory complications after research bronchoscopy performed in patients with COPD ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…The Subpopulations Intermediate Outcome Measures in COPD Study (SPIROMICS) is a prospective cohort study that has enrolled 2981 subjects across four strata (1) Never smokers (NS), (2) Current or former smokers without COPD (HS), (3) Mild/Moderate COPD, and (4) Severe COPD). Goblet Cell Density (GCD) was measured in 71 subjects in strata 2-4 (current or former smokers with and without COPD) in which endobronchial mucosal biopsies were obtained during the SPIROMICS bronchoscopy substudy 13 . Methods of measuring GCD were performed as previously described 8 .…”
Section: Methodsmentioning
confidence: 99%
“…BAL was performed in the right middle lobe and lingula by instilling two aliquots of 40 mL and one aliquot of 50 mL per lobe (260 mL total volume), after excluding an initial airway wash sample. Unfiltered BALF fluid was collected into a sterilized beaker or in multiple 50 mL conical tubes on ice, then centrifuged at 300 x g for 5 min and the supernatant aliquoted into 1 mL aliquots for storage at −80 °C, representing one BALF sample per patient as described previously 63,64 . Because no research plasma samples were obtained in the bronchoscopy sub-study, the plasma biomarkers, including ferritin, in this analysis were measured from the baseline visit samples.…”
Section: Discussionmentioning
confidence: 99%